2020
DOI: 10.7717/peerj.9579
|View full text |Cite
|
Sign up to set email alerts
|

Gluconobacter dominates the gut microbiome of the Asian palm civet Paradoxurus hermaphroditus that produces kopi luwak

Abstract: Coffee beans derived from feces of the civet cat are used to brew coffee known as kopi luwak (the Indonesian words for coffee and palm civet, respectively), which is one of the most expensive coffees in the world owing to its limited supply and strong market demand. Recent metabolomics studies have revealed that kopi luwak metabolites differ from metabolites found in other coffee beans. To produce kopi luwak, coffee beans are first eaten by civet cats. It has been proposed that fermentation inside the civet ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Gluconobacter was recently identified as the main microbial group in the faeces of the civet cat ( Paradoxurus hermaphroditus ) used to produce kopi luwak coffee, which is generated by the cleaning, drying, and roasting the coffee beans that were excreted in faeces by this animal. The authors suggested that the colonization of AAB in the gut of civet cat was related with the diet based on ingestion of coffee cherries containing these microorganisms (Watanabe et al ., 2020). Kopi luwak coffee is considered one of the most expensive commodities among the coffee matrix, and metabolomic approaches revealed the presence of discriminant markers commonly produced by Gluconobacter , such as glycolic and malic acid (Wei et al ., 2009; Turkia et al ., 2010; Jumhawan et al ., 2013; Putri et al ., 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gluconobacter was recently identified as the main microbial group in the faeces of the civet cat ( Paradoxurus hermaphroditus ) used to produce kopi luwak coffee, which is generated by the cleaning, drying, and roasting the coffee beans that were excreted in faeces by this animal. The authors suggested that the colonization of AAB in the gut of civet cat was related with the diet based on ingestion of coffee cherries containing these microorganisms (Watanabe et al ., 2020). Kopi luwak coffee is considered one of the most expensive commodities among the coffee matrix, and metabolomic approaches revealed the presence of discriminant markers commonly produced by Gluconobacter , such as glycolic and malic acid (Wei et al ., 2009; Turkia et al ., 2010; Jumhawan et al ., 2013; Putri et al ., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the high energetic efficiency, the oxidative metabolism of glucose and alcohols produces intermediate products, such as 2‐methyl‐butanoic acid and gluconic acid, that are precursors of several flavour‐active compounds associated with desirable fruity aroma (Keliang and Dongzhi, 2006). Finally, the detection of citric acid only at 24 h can be resulted of the incomplete tricarboxylic acid (TCA) cycle in Gluconobacter due to the lack of succinate hydrogenase, which leads to the accumulation of citrate in the extracellular matrix (Watanabe et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the high price has caused an increased hunting of Luwak animals. For this reason, the use of starter cultures with species of Gluconobacter, Lactobacillus, Leuconostoc, and Streptococcus isolated from the intestinal tract of Luwaks, have been proposed [55,56].…”
Section: Coffeementioning
confidence: 99%
“…Sugar, protein, and pectin are degraded into simpler forms with the aid of digestive enzymes; studies have, moreover, isolated the microbial strains in the biomass from palm civets, which are responsible for the catabolism of caffeine in the coffee bulb via N -demethylation and xanthine oxidation [ 6 ]. Gluconobacter species possessing genes that encode enzymes for the metabolism of sulfur-containing amino acids have been reported in palm civet feces [ 7 ]. The degradation of structural polysaccharides eases the penetration of fermented metabolites into coffee beans.…”
Section: Introductionmentioning
confidence: 99%